KANDUNGAN SENYAWA FLAVONOID DAN ANTOSIANIN EKSTRAK KAYU SECANG (Caesalpinia sappan L.) SERTA AKTIVITAS ANTIBAKTERI TERHADAP Vibrio cholerae - Nomer, Ni Made Gress Rakasari; Duniaji, Agus Selamet; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
The aim of this research to determine the concentration of flavonoid and anthocyanin compounds in sappan wood extract (Caesalpinia sappan L.), as well as to determine the concentration of inhibitory power against the growth of Vibrio cholerae. This experimental design study uses 5 kind of concentration, which are 20%, 40%, 60%, 80%, 100%. The analysis were repeated 3 times and resulting in 15 experimental units. The data were presented in descriptive statistic with tables, drawings and discussed. The results showed that the extract of sappan wood contained flavonoid compounds of 6,02%, anthocyanin compounds of 2,43% and was able to inhibit the growth of Vibrio cholerae with optimal concentration at a concentration of 80% with an average 20,1 mm and very strong inhibition categories.